Contemporary evaluation of mitral regurgitation – 3D echocardiography, cardiac magnetic resonance, and procedural planning. (2nd September 2017) - Corrigan, Frank E.; Maini, Aneel; Reginauld, Shawn; Lerakis, Stamatios
ABSTRACT: Introduction : Mitral regurgitation is one of the more common forms of valvular heart disease. Given the expansion of therapies for structural heart disease, new therapies for mitral regurgitation are emerging. An accurate description and classification of mitral disease is important to understand pathology and provide recommendations for therapy. Areas covered : In the modern evaluation of mitral regurgitation, 3-dimensional echocardiography (3DE) and cardiac magnetic resonance imaging (CMR) play important roles which overcome the prior limitations of 2-dimensional echocardiography. Specifically, an advanced evaluation with these techniques allows accurate characterization of the anatomic etiology of mitral regurgitation and quantification of severity. Furthermore, the role of 3DE during intraprocedural guidance, 'interventional echocardiography, ' is expanding. Expert commentary : In our review, we demonstrate a complete diagnostic evaluation of mitral valve dysfunction by 3DE and CMR and describe current implications for invasive therapy and procedural guidance.